2011
DOI: 10.2500/aap.2011.32.3450
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and safety of drug provocation tests

Abstract: Drug provocation tests (DPTs) are considered the gold standard for identifying adverse drug reactions (ADRs). The aim of this study was to analyze DPT results and discuss severe systemic reactions associated with them. This was a retrospective analysis of 500 patients with ADRs who sought treatment and were submitted to DPTs when indicated between 2006 and 2010. We performed DPTs according to the European Network for Drug Allergy recommendations. Single-blind, placebo-controlled DPTs were performed with antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 15 publications
3
23
1
3
Order By: Relevance
“…The ADR rates of 11% for test doses and 12% for multistep challenges in our study fall between rates of 4.1% and 16% reported in prior studies. 9,10 Unlike other studies, no anaphylactic reactions occurred with test doses or multistep challenges, which underlies the importance of careful review and evaluation of a patient's drug allergy history before performing test doses or challenges. 10 Our findings, therefore, demonstrated that test doses are safe for evaluation of ADRs and that multistep challenges do not confer additional safety.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The ADR rates of 11% for test doses and 12% for multistep challenges in our study fall between rates of 4.1% and 16% reported in prior studies. 9,10 Unlike other studies, no anaphylactic reactions occurred with test doses or multistep challenges, which underlies the importance of careful review and evaluation of a patient's drug allergy history before performing test doses or challenges. 10 Our findings, therefore, demonstrated that test doses are safe for evaluation of ADRs and that multistep challenges do not confer additional safety.…”
Section: Discussionmentioning
confidence: 95%
“…9,10 Unlike other studies, no anaphylactic reactions occurred with test doses or multistep challenges, which underlies the importance of careful review and evaluation of a patient's drug allergy history before performing test doses or challenges. 10 Our findings, therefore, demonstrated that test doses are safe for evaluation of ADRs and that multistep challenges do not confer additional safety. Advantages of 1-or 2-step test doses over multistep challenges include the lack of concern for induction of tolerance or desensitization; the requirement for fewer resources, such as staffing and time; and the ability for inpatients to reach therapeutic dosing more rapidly.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…9,12-16 One study reported a 16% subjective reaction rate with a 0.8% true reaction rate, 12 whereas other studies reported an overall reaction rate between 4.1% and 12%. 9,13,17 Despite the extensive use of graded challenges for the evaluation of ADRs, evidence-based guidelines regarding optimal protocols are lacking. 8 A study published in 1992 of patients with historical penicillin reactions and subsequent negative skin testing used a 2-step active challenge composed of a subcutaneous test dose of 5 mg of penicillin followed by a full therapeutic dose.…”
mentioning
confidence: 99%
“…17 Other challenges reported in the literature range from Abbreviations used ADR-Allergic drug reaction NSAID-Nonsteroidal anti-inflammatory drug administration of single therapeutic doses to multiple doses over several days with variable use of placebo. 9,[12][13][14][15][16]18 Concern exists that challenges composed of more than 4 steps may lead to an induction of tolerance. 6 A recent noneplacebo-controlled study demonstrated that a 2-step graded challenge is as safe as a 3-or 4-step graded challenge with a reaction rate of 11% versus 12%, respectively.…”
mentioning
confidence: 99%